ALTERNATIF PENYELESAIAN SENGKETA BATAS BIDANG TANAH DAN UPAYA PENYELESAIANNYA - Siti Parlina; Devi Siti Hamzah (JURNAL ILMIAH LIVING LAW, 2023)
Dispute settlement is the settlement of a case that is settled between one party and another, the purpose of the debate can be pursued through a lawsuit (settlement through court) and non-prosecution (settlement is done out of court). The motivation behind this examination is to find out how the exchange of land rights without a will and how the alternative settlement of land problems that occur on the land of the poor is ensured. The research technique used is normative juridical The exchange of land rights without ratification can be done through time intervals, where this technique does not require a statement as strong evidence, but the litigants in land disputes can show that they have developed or have given legal authority and has been dealing with soil properly for a long time. (twenty years) to 30 (thirty years) and Settlement of land problems that occur on land that have been guaranteed to be carried out through deliberation/thought, conciliation, mediation and arbitration. By regulation, land that does not have a will cannot be considered as the property of the person who controls it.  Keywords : Land disputes; litigation; non-litigation